POTENSI PERMUDAAN SEMAI PADA HUTAN YANG DIKELOLA DENGAN SISTEM SILVIKULTUR TPTJ DI KALIMANTAN TENGAH Entitled Potential for Nature Seedling Regeneration in The Forest that Managed by Silviculture System of TPTJ in Central Kalimantan - Prijanto Pamoengkas; Ahmad Iyyannanda Fatir Assifa (Jurnal Silvikultur Tropika, 2018)
Forest management activity wich applied selective cutting with line planting (TPTJ) caused disturbed on forest, especially due to the process of making the planting lines. Natural forest gives respond to disturbance by recovery of its vegetation. This research aimed to measure the potential seedlings by vegetation recovery process in logged over area and determine both of the diversity and evenness of communities. The result showed that the composition of the seedlings at the begining of a recovery in the cropping were not only pioneer, but also kinds of Dipterocarpaceae and non-Dipterocarpaceae. The entire lines is dominated by the pioneers types, such as: Macaranga gigantea, Ganua glaberrima, Aporosa apriniana and Polyalthia rumphii. The family with the most number of types found namely: Phyllanthaceae, Myrtaceae and Dipterocarpaceae. The value of diversity index all of community belongs to moderate ( 2 < H’ < 3) and value equity (e’) belongs to high. The entire community of between the lines have low IS value wich its IS < 50% that means tampering with the seedling in each line has a significant different due to the forest examined was divided into several blocks of high fells.Keywords : climax, diversity, equity, pioneer, selective cutting with line planting